Pengenalan Argot: Komunikasi Terselubung Komunitas Pengguna NAPZA - Astri Widyaruli Anggraeni; Kristi Nuraini; Adetya Pratika Aprilia; Andini Cahyaningrum (Indonesian Journal Publisher, 2023)
This socialization is carried out in line with the development of increasingly sophisticated digital and communication technology, by showing how easy anything is done nowadays. One of which is the circulation of narcotics and illegal drugs whose circulation is concealed and is common among teenagers. The purpose of this provision is to increase insight, knowledge, public awareness, and effective communication, especially for teenagers regarding the dangers on the use of Narcotics, Psychotropics, and Addictive Substances (Drugs). The method of the provision is carried out through two stages (1) preparation, it is done by preparing selected materials as well as the presentation of the chosen materials by the team. (2) Having online socialization through zoom meeting from the team to the participants. This activity is also to celebrate the 20th Anniversary of BNN RI. The result of this provision activity is increasing public awareness, especially teenagers about the dangers of drugs. This can be seen from the discussion session, especially the use of argot in the drug community, which has become a valuable insight for participants.